Aphasic mild cognitive impairment in prodromal dementia with Lewy bodies - Watanabe, Hiroyuki; Hikida, Sakura; Ikeda, Manabu; Mori, Etsuro (Frontiers in Neurology, 2023)
Introduction This study aimed to determine the characteristics of aphasic mild cognitive impairment (aphasic MCI), which is characterized by a progressive and relatively prominent language impairment compared with other cognitive impairments, in the prodromal phase of dementia with Lewy bodies (DLB). Methods Of the 26 consecutive patients with aphasic MCI who had been prospectively recruited at our hospital, 8 patients were diagnosed with prodromal DLB and underwent language, neurological, neuropsychological, and neuroimaging (N-isopropyl-p-[123I] iodoamphetamine single-photon emission computed tomography; IMP-SPECT) testing. Three of these patients also underwent cholinesterase inhibitor therapy with donepezil. Results In our aphasic MCI cohort, the clinical diagnosis of probable prodromal DLB accounted for more than 30% of cases; therefore, the presence of language impairment in prodromal DLB was not very uncommon. Five patients were diagnosed with progressive anomic aphasia and three with logopenic progressive aphasia. Anomic aphasia was characterized by apparent anomia but relatively preserved repetition and comprehension ability and logopenic progressive aphasia by anomia, phonemic paraphasia, and impaired repetition. IMP-SPECT revealed hypoperfusion of the temporal and parietal lobes in the left hemisphere in all but one patient. All patients who underwent cholinesterase inhibitor therapy with donepezil showed improvement in general cognitive function, including language function. Discussion The clinical and imaging features of aphasic MCI in prodromal DLB are similar to those observed in Alzheimer's disease. Progressive fluent aphasia, such as progressive anomic aphasia and logopenic progressive aphasia, is one of the clinical presentations in prodromal state of DLB. Our findings provide further insight into the clinical spectrum of prodromal DLB and may contribute to the development of medication for progressive aphasia caused by cholinergic insufficiency.